COMPARATIVE ANALYSIS OF THYROID FUNCTION PROFILES BETWEEN POLYCYSTIC OVARY SYNDROME PATIENTS AND HEALTHY CONTROLS: A COMPREHENSIVE STUDY - Kaur, Amandeep; Singh, Tejinder; Kaur, Komalpreet; Kaur, Sukhjeet (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To assess the thyroid function status of patients with Polycystic Ovary Syndrome (PCOS) and to compare it with that of healthy women. Methods: This was a descriptive cross-sectional study conducted in the Department of Biochemistry in collaboration with the Department of Obstetrics and Gynecology of a tertiary care hospital in Northern India. 30 patients diagnosed to have polycystic ovarian syndrome on the basis of the Rotterdam criteria were included in this study as cases (Group P). 30 healthy women were enrolled as the control group (Group H). The mean age and marital status of the patients were assessed. The body mass index of all the patients was also determined and compared. Systolic blood pressure, diastolic blood pressure, and pulse rate were also compared. A thyroid function test was done in both groups. The mean triiodothyronine (T3), T4, and thyroid-stimulating hormone (TSH) levels were compared in both groups. p<0.05 was taken as statistically significant. Results: The mean age of patients with PCOS and healthy individuals was 22.10±3.97 years and 23.76±3.97 years, respectively. The mean ages of both groups were found to be comparable in both studies (p=0.1108). The mean body mass index (BMI) of groups P and H was found to be 27.23±5.82 and 23.15±4.12, respectively. The women in group P were found to have a higher BMI as compared to women in group H, and the difference was found to be statistically significant (p=0.0027). The mean pulse rate, systolic blood pressure, and diastolic blood pressure values were found to be comparable. The mean FT3 levels in groups P and H were found to be 3.11±0.88 and 3.13±0.42 ng/mL, whereas the mean free thyroxine levels in groups P and H were found to be 0.96±0.16 and 0.89±0.15, respectively, μg/dL. The mean T3 and T4 levels of both groups were found to be comparable in both groups. However, the mean TSH level in groups P and H was found to be 4.95±2.24 and 2.50±1.19 0.3–4.5 μIU/ml, respectively. The mean TSH level in group P was found to be higher than group H, and the difference was found to be statistically significant (p<0.001). Conclusion: The prevalence of subclinical hypothyroidism was found to be significantly high in women with PCOS, making it necessary to do periodic thyroid function tests in PCOS.